Living Hadis Larangan Tidur Setelah Sholat Ashar Pada Santri Pondok Pesantren Madinatul Munawwarah Bukittinggi - Husna Husna; Riri Fitria; Taufiqurrahman Taufiqurrahman (Jurnal Budi Pekerti Agama Islam, 2024)
The discussion in this research is, what is the quality of the hadith and students' understanding of the hadith regarding the prohibition of sleeping after Asr prayer that applies to students at the Madinatul Munawwarah Islamic Boarding School, Bukittinggi. The author limited the research informants to students who had ranks one to ten at the Tsanawiyah and Aliyah levels. The aim of writing this research is to determine the quality of the sleep prohibition hadith that applies to students at the Madinatul Munawwarah Islamic Boarding School, as well as the students' implementation of the sleep prohibition hadith after the Asr prayer. This research uses a qualitative type of research using a sociology of knowledge approach. This research is field research. This was taken with the aim of finding out the hadith on the prohibition of sleeping after the Asr prayer that applies at the Madinatul Munawwarah Islamic Boarding School and knowing the quality of the hadith on the prohibition of sleeping after the Asr prayer. Based on the data obtained, there are three hadiths regarding the prohibition of sleeping after Ashar prayers that apply at the Madinatul Munawwarah Islamic Boarding School. The first hadith is narrated by the As-Shuyuti Book which is of dhaif quality and has many lines of narration so that the hadith is at the hasan lighairihi level, the second hadith narrated by Ath-Thabrani is included in the group of gharib ahad hadiths, and the third hadith explains the virtues of using time in the afternoon, and this hadith is found in the book of Imam Muslim and is of authentic quality. The hadith regarding the prohibition of sleeping after the Asr prayer is of dhaif quality but can be practiced by santriwan and female students by participating in various activities such as extracurriculars and other useful activities, and the hadith can be practiced in matters of fadhailul charity, in terms of motivating.